A basic guide to hospitalising snakes. Issue 3 (3rd March 2016) - Valentine, Adina
Abstract: In small animal first opinion practice we occasionally see patients of the furless and legless variety. Often portrayed as the 'stuff of nightmares' our serpent friends have a bad reputation, and, formost, are not at the top of the list of our favourite animals. Unfortunately, the majority of the reptilian patients that grace our surgeries have fallen foul of poor basic husbandry, which is left for us to discover and fix. This article aims to give a basic guide to hospitalising some of the more common reptile species seen in veterinary practice and addresses the essential questions that need to be asked on admission as taking a detailed history of the husbandry is an essential part of the diagnostic process. .